Mekanisme kerja beberapa pestisida dan penanggulangan keracunannya pada manusia - R.H.Yudono R.H.Yudono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1978)
Although the pesticides are for the purpose of killing pest ( = unwanted forms of life), they are also toxic to many non target species, including man. In fact acute or chronic poisoning by pesticides does occur. This is usually the result of occupational exposures or careless use, misuse or mishandling of the pesticides.As with the use of any potentially injurious chemical substance, the use of pesticides must take into consideration the balance of the benefits that may be expected versus the possible risk of injury to human health or to degradation of environmental quality.The prospect of mass starvation due to destruction of food crops by insects and noxious weeds compared to the question of possible injury to a few members of the population as a result of the use of insecticides may clearly indicate an advantage of pesticide use in terms of numbers of people whose health and welfare are protected. Similarly where vector borne diseases are a major threat to the health of large human populations and where the use of chemical pesticides to destroy the vectors of these diseases is a successful procedure, the application of these chemicals seems to beclearly indicated.For some groups of pesticides the mechanism of toxic action is well understood, but for others there is little or essentially no information concerning the way of intoxication.Concerning treatment, as might be expected from the current knowledge of pathogenesis, it is also not always easy CO find the right one. For this reason, if possible, we should better prevent than treat intoxication from pesticides or if we are forced to use pesticides, we must make our choice among the non-toxic pesticides or which intoxication is treatable.